Influence of red mud on fresh and hardened properties of self-compacting concrete. (30th July 2018) - Tang, W.C.; Wang, Z.; Liu, Y.; Cui, H.Z.
Highlights: The influence of red mud on fresh and hardened properties of SCC were studied. High superplasticiser dosages required for red mud concrete to meet the SCC requirements. Mechanical strength of concrete slightly increased with increasing red mud content. No significant difference of ITZ for red mud concrete compared to the control. Some albite crystals appearing in triclinic shape were identified by XRD in red mud concrete. Abstract: Red mud is a waste product from the production of alumina, it currently has limited industrial use. This study proposed to use red mud to partially replace fly ash (12.5, 25 and 50% by weight) in self-compacting concrete (SCC) and the influence of red mud on the fresh and hardened properties and microstructural behaviour of SCC were studied. Slump-flow, T500 and J-ring tests were carried out on fresh SCC mixtures. The hardened properties of red mud SCCs including compressive strength, tensile strength and elastic modulus were studied. Moreover, the chemical composition and microstructural properties of red mud concrete samples were analysed using X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS), respectively. The results show that the mechanical strength of concrete increased with increasing red mud content. SCC samples consisting 50% red mud performed the best for the compressive strength and elastic modulus. The results from microscopic studies indicated that there was a slight improvement in the interfacial transition zone (ITZ) between aggregate and cement paste for red mud concrete compared with control concrete. The XRD results indicated that the chemical composition of cement paste containing red mud showed higher sodium and iron contents. With increasing red mud content, some albite crystals appearing in triclinic shape were also identified by XRD.